Current trends in Anterior Cruciate Ligament reconstructions - Dawid Merkiel; Piotr Walus; Piotr Piech; Paweł Polak; Robert Węgłowski; Wojciech Grodzicki; Piotr Flis; Przemysław Sławiński; Kamil Fatyga; Maciej Kozioł (Kazimierz Wielki University, 2018)
The rupture of the Anterior Cruciate Ligament (ACL) is a common complication of knee trauma. Arthroscopic ACL reconstructive surgery is the method of choice in most of these cases. This is an increasingly common procedure due to low invasiveness, good treatment results and a constantly growing number of operators able to perform them. The aim of the study is to review currently used methods for the reconstruction of the Anterior Cruciate Ligament. There are many types of transplants, and the choice depends on individual factors (including gender, age, occupation, physical activity) and the patient's expectations. The operator's skills and preferences also determine the choice of therapy. Considering the above-mentioned aspects, authors of the study will analyze ACL reconstruction methods based on the latest literature. Currently, the basic treatment of ACL injuries are arthroscopic procedures. Due to the various types of transplants, the procedure, result and complications may vary depending on the choice. An autograft is the preferred treatment for this injury. Autografts that are prefered are the ligaments of the semitendinosus muscle and the patellar tendon. Less frequently used autografts include ligaments of the quadriceps muscle of the thigh and gastrocnemius muscle (Achilles tendon). Another type of transplant is an allograft. The graft is taken from a donor (a deceased donor in cases of ligament transplants). It is less frequently used due to its high cost, lower strength compared to an autograft and a greater number of complications. The third type of transplants are synthetic grafts. These are fibers made of materials such as Gore-Tex. Synthetic grafts are also rarely used for the same reasons as allografts. Internal Bracing (IB) is becoming a more popular procedure. This method allows you to re-attach broken ligaments in their original position. This is possible if only one end of the ligament is broken. An important issue is the number of bundles (single-bundle, double-bundle), the position and the type of attachment (titanium screws, absorbable, endobutton). The final choice of the treatment method depends on the operator's skills and preferences.